GENETIC POLYMORPHISMS INFLUENCING EFFICACY AND SAFETY OF METHOTREXATE IN RHEUMATOID ARTHRITIS - B, Premkumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This review will summarize pharmacogenetic studies of single nucleotide polymorphisms in genes coding enzymes of methotrexate (MTX) pathway, related to its response and toxicity in rheumatoid arthritis (RA). In addition, this review focuses on the racial and ethnic differences in distribution of the polymorphisms in genes related to efficacy and toxicity of MTX in RA. Methods: Articles were searched using Pubmed database using the search term pharmacogenetics and MTX and arthritis.â€ The search revealed 72 articles, of which 27 were given special importance, due to open-access. Results: Many genes and single nucleotide polymorphisms are investigated in this context, and the highlighting genes are ATP-binding cassette proteins (ABCB1) reduced folate carrier (RFC), methylenetetrahydrofolatereductase (MTHFR), gamma-glutamyl hydrolase (GGH), serine hydroxyl methyltransferase (SHMT), 5-aminoimidazole-4-carboxamide ribonucleotidetransformylase (ATIC), methionine synthase reductase (MTRR), methionine synthase (MS), adenosine monophosphate deaminase1 (AMPD1), inosine triphosphate pyrophosphatase (ITPA). The study highlighted RFC-1 80AA, ITPA 94CC, and AMPD1 347CC as responders. The allelic types prone to toxicity were MTHFR 677TT, MTRR 2756AA, MS 66GG, SHMT 1420CC, ATIC 347GG, and thymidylate synthase *3/*2. The genotypes reported as non-responders were ABCB1 3434TT, MTHFR 1298AA, DHFR A317G, GGH 16CC, and GGH 401TT. Conclusion: Although these studies highlight inconsistency in results, due to the difference in sample size and assessment parameters and racial and ethnic differences, larger prospective studies are essential to reach the cornerstone of the concept of personalized medicine.